Intra-articular treatment with corticosteroids increases apoptosis in human rotator cuff tears. (4th May 2019) - Ramírez, Juan Pablo; Bonati-Richardson, Francesca; García, María Pía; Hidalgo, Christian; Stoore, Caroll; Liendo, Rodrigo; Soza, Francisco; Landerer, Eduardo; Paredes, Rodolfo
ABSTRACT: Purpose : The aim of this study is to evaluate in vivo the level of apoptosis in human rotator cuff tears and the relationship it might have with tendon degeneration. Methods : Rotator cuff biopsies from 19 male and female patients, ages between 38 and 68 years, with and without previous corticosteroid infiltrations were collected via arthroscopy. Biopsies from seven patients with healthy rotator cuffs were used as a control group. An in situ terminal deoxynucleotidyl transferase dUTP nick end labeling assay was performed to detect the level of apoptosis, which was expressed as a percentage of apoptotic cells (PAC). Results : PAC in patients with corticosteroid infiltrations was 76.97 ± 16.99 in all tendon rupture zones, in non-infiltrated patients was 35.89 ± 22.96, whereas in control patients was 14.48 ± 8.15. Likewise, the tendency of PAC reveals that apoptosis in control and non-infiltrated groups was different and dispersed in all tear zones; while in corticosteroid treated patients, the tendency was similar in all rupture sites. Conclusions : This investigation leads us to conclude that the administration of corticosteroid is associated with a higher amount of apoptosis at the insertion site of the rotator cuff (rupture edge).